OBSERVATION OF UTERINE INVOLUTION IN ETAWA CROSSBREED GOATS (Capra hircus) USING TRANSCUTANEUS ULTRASONOGRAPHY - Juli Melia; Ayu Wannisa; Tongku Nizwan Siregar; Hafizuddin Hafizuddin; Budianto Panjaitan; Arman Sayuti; Syafruddin Syafruddin (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2020)
The aim of this study was to observe the uterine involution of Etawa crossbreed (PE) goat using transcutaneous ultrasonography (USG). This study used four postpartum female goats that released placenta normally. The goats were examined on lateral recumbence position. Uterine involution was observed daily. The study began from the first day of postpartum period until there were no more reduction of uterine horns lumen diameter. From the 1st to 7th day of postpartum period, ultrasound imaging of the uterine wall showed caruncle which was hypoechoic, lumen of uterine filled with lochia (the image was hypoechoic to anechoic) and a clearly visible uterine horns lumen which had decreased in diameter from 105.9 ± 0.9 mm to 87.2 ± 4.6 mm. From the 8th day to the 14th day, lumen diameter had decreased from 80.4 ± 3.8 mm to 63.6 ± 3.2 mm. The presence of caruncle was reduced and the amount of lochia was decreased (anechoic). From the 15th day to the 21st day, lumen diameter had decreased from 61.4 ± 2.1 mm to 52.1 ± 2.7 mm, and the remnants of caruncle and lochia were still visible. From the 22nd day to the 26th day, the diameter of the uterine wall had decreased from 49.7 ± 0.6 mm to 41.5 ± 6.7 mm, and the lochia and caruncle were no longer visible. From the 26th to the 30th day, uterine horns lumen diameter had still decreased from 41.5 ± 6.7 mm to 31.7 ± 0.9 mm. Uterine horns lumen diameter size had decreased every day, stabilized on the 30th day, and ceased to decrease on the 31st day, where the diameter size was the same as on the 30th day postpartum (31.7 ± 0.9 mm). It can be concluded that the duration of uterine involution in PE goats, which had normal delivery is 30-31 days.